The Liverwort, Marchantia, Drives Alternative Electron Flow Using a Flavodiiron Protein to Protect PSI. Issue 3 (2nd February 2017) - Shimakawa, Ginga; Ishizaki, Kimitsune; Tsukamoto, Shigeyuki; Tanaka, Moeko; Sejima, Takehiro; Miyake, Chikahiro
Abstract : Flavodiiron protein drives an oxygen-dependent alternative electron flow to stimulate the protective mechanisms of PSI against photooxidative damage in the liverwort Marchantia polymorpha. Abstract: The diffusion efficiency of oxygen in the atmosphere, like that of CO2, is approximately 10 4 times greater than that in aqueous environments. Consequently, terrestrial photosynthetic organisms need mechanisms to protect against potential oxidative damage. The liverwort Marchantia polymorpha, a basal land plant, has habitats where it is exposed to both water and the atmosphere. Furthermore, like cyanobacteria, M. polymorpha has genes encoding flavodiiron proteins (FLV). In cyanobacteria, FLVs mediate oxygen-dependent alternative electron flow (AEF ) to suppress the production of reactive oxygen species. Here, we investigated whether FLVs are required for the protection of photosynthesis in M. polymorpha . A mutant deficient in the FLV1 isozyme (Ɗ MpFlv1 ) sustained photooxidative damage to photosystem I (PSI) following repetitive short-saturation pulses of light. Compared with the wild type (Takaragaike-1), Ɗ MpFlv1 showed the same photosynthetic oxygen evolution rate but a lower electron transport rate during the induction phase of photosynthesis. Additionally, the reaction center chlorophyll in PSI, P700, was highly reduced in Ɗ MpFlv1 but not in Takaragaike-1. These results indicate that the gene product of MpFlv1 drives AEF to oxidize PSI, as in cyanobacteria. Furthermore, FLV-mediated AEF supports the production of a proton motive force to possibly induce the nonphotochemical quenching of chlorophyll fluorescence and suppress electron transport in the cytochrome b 6 / f complex. After submerging the thalli, a decrease in photosystem II operating efficiency was observed, particularly in Ɗ MpFlv1, which implies that species living in these sorts of habitats require FLV-mediated AEF .